Post-cyclone (Aila), transforming lives and gendered relations in Bangladesh. (28th April 2021) - Roy, Sajal; Mathbor, Golam M
Abstract: This study examines the long-term effects of Cyclone Aila on the traditional livelihood of the Munda community in the Sundarbans forest of Bangladesh, together with its socially and culturally assigned gendering. Building on existing critiques of gender and critical developmental studies, the present study uses an ethnographic approach and traces resilience alongside a new gender equality between males and females, as they jointly discover new commercial and home industry occupations to replace the damaged Sundarbans forest heritage, discarding gendered role stereotypes in the jobs they do and the way they contribute to family income.